PROSES KREATIF EKSTRAKULIKULER MUSIKALISASI PUISI DI SMK K.H A WAHAB MUHSIN TASIKMALAYA - Nurdin, Ali (Jurnal Seni dan Pembelajaran, 2023)
This study aims to find out the process of poetry musical extracurricular activities at K.H A Wahab Muhsin Vocational School and how to foster students' interest in poetry music extracurricular activities. This study uses a qualitative method with an analytic descriptive approach. with data collection techniques using observation, interviews, documentation and literature study. The results of this study are extracurricular activities outside of school hours and still included in formal education at school. These extracurricular activities are no less important than intracurricular activities, because by participating in these extracurricular activities students are given the opportunity by the school to further develop their talents, interests and hobbies that students like. There are various kinds of extracurricular activities in school, one of which is Poetry Musicalization. Poetry musicalization is a way of conveying poetry by turning a poem into a song. The musical arrangement used must also be in harmony with the meaning of the poem to be conveyed. But on the other hand, for musical instruments there are no limitations for using any musical instrument. For the instruments used at K.H A Wahab Muhsin Vocational School, they use non-conventional musical instruments, namely musical instruments that are not as usual. Keywords: Extracurriculars, Poetry Musicalization, Non-Conventional Musical Instruments.